Capital adjustment cost and inconsistency in income‐based dynamic panel models with fixed effects. Issue 4 (14th August 2019) - Basu, Parantap; Bhattarai, Keshab; Getachew, Yoseph
Abstract: After the seminal work of Nickell (1981), a vast literature demonstrates the inconsistency of 'conditional convergence' estimator in income‐based dynamic panel models with fixed effects when the time horizon ( T ) is short but the sample of countries ( N ) is large. Less attention is given to the economic root of inconsistency of the fixed effects estimator when T is also large. Using a variant of the Ramsey growth model with long‐run adjustment cost of capital, we demonstrate that the fixed effects estimator of such models could be inconsistent when T is large. This inconsistency arises because of the long‐run adjustment cost of capital which gives rise to a negative moving average coefficient in the error term. Income convergence will be thus overestimated. We theoretically characterize the order of this inconsistency. Our Monte Carlo simulation demonstrates that the size of the bias is substantial and it is greater in economies with higher capital adjustment costs. We show that the use of instrumental variables that take into account the presence of the negative moving average term in the error will overcome this bias.